التعاون الدولي في مواجهة جريمة الإتجار بالأدوية المزيفة - عيسى, حسين عبدعلي; أمين, هەڵاڵه محمد تقي محمد (Sulaimani Journal for Humanities, 2018)
This study shows the essential nature of the criminal trading with counterfeit medicaments, by clarifying the Terminology of counterfeit medicines, the associated risks, and the reasons for its exacerbation. The research does attempt to present international cooperation to confront it by focusing on the role of international and regional organization. The study composed from; introduction, two subsections, and termination. The first subsections shed the light upon the essential nature of the criminal trading with counterfeit medicaments. While the second subsection looks into more detail at the role of the international and regional organization in tackling such crime. The termination included the conclusions and recommendations associated with it.